Run-time modelling of energy consumption in mobile robots : Technical report - 2024 - Malik, Abdul; Haghbayan, Hashem; Plosila, Juha (fi=Turun yliopisto|en=University of Turku|, 2024)
In recent years, the deployment of mobile robots in various industries, from manufacturing to healthcare, has seen a significant rise. This necessitates an in-depth understanding of their energy consumption patterns to optimize efficiency and sustainability. This report presents a comprehensive platform developed to measure and analyze the electric current consumed by both the computational and mechanical components of mobile robots. At first, the project focuses on developing a mobile rover by integrating NVIDIA Jetson Nano, Pixhawk 4 Flight Controller along PM07 Power management Board on a Reely rover. Secondly, a runtime current measuring system has been developed using HSTS016L current sensor, ADS1115 ADC along with NVIDIA Jetson Nano. The primary aim of this study is to provide a detailed and accurate model for run-time energy consumption measurement. Additionally, this report covers the methodology for measuring system dynamics i.e. distance, velocity, acceleration and jerk using GPS data, processed through both the Haversine method and Python’s Pyproj library. This dual-method approach enhances the accuracy of distance measurement, crucial for correlating energy consumption with the rover’s operational parameters. The study can be further extended to study real-time energy consumption of autonomous robots in different autonomous applications. Keywords: Energy Consumption, Mobile Robots, Jetson Nano, System Dynamics